2022
DOI: 10.31004/obsesi.v6i4.2321
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Mempengaruhi Parental Self-Efficacy Orang Tua Yang Memiliki Anak dengan Disabilitas

Abstract: Adanya kebutuhan unik dari anak dengan disabilitas menghadapkan orang tua pada risiko permasalahan fisik dan mental dalam pengasuhan. Parental self-efficacy menjadi salah satu faktor penting untuk menurunkan distress psikologis dan perilaku maladaptif dalam pengasuhan. Artikel ini bertujuan untuk mengetahui faktor yang mempengaruhi Parental self-efficacy. Penelitian dilakukan dengan metode systematic review menggunakan framework PICO dalam menentukan kriteria inklusi dan eksklusi. Pencarian artikel dilakukan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This research shows that the age of circular migrant worker fathers has a significant positive relationship with paternal self-efficacy, which means that the higher the age of circular migrant worker fathers, the higher the paternal self-efficacy of circular migrant worker fathers. This is in line with Harita and Chusairi (2022) that fathers use parental self-efficacy as a shield to reduce stress and depression in parenting. The older the father is, the higher the parental self-efficacy he has, so the lower the stress and depression he experiences.…”
Section: Discussionsupporting
confidence: 86%
“…This research shows that the age of circular migrant worker fathers has a significant positive relationship with paternal self-efficacy, which means that the higher the age of circular migrant worker fathers, the higher the paternal self-efficacy of circular migrant worker fathers. This is in line with Harita and Chusairi (2022) that fathers use parental self-efficacy as a shield to reduce stress and depression in parenting. The older the father is, the higher the parental self-efficacy he has, so the lower the stress and depression he experiences.…”
Section: Discussionsupporting
confidence: 86%
“…Mr So, who agreed to increase the number of their children, could provide emotional support for Mrs So. The results showed that partner support in the form of attention, assistance, and partner involvement reduced the pressure experienced by mothers in caring for children with disabilities (Leung, 2020;Harita & Chusairi, 2022). Social support is an important element in a healthy communication system to be able to express feelings, listen, and respect each other (Olson et al, 2019).…”
Section: Dimensions Of Flexibility Olson Circumplex Modelmentioning
confidence: 99%
“…Support from spouse and family can affect the maternal parenting self-efficacy (Hong & Liu, 2021). Attention, assistance, and partner involvement reduce the pressure experienced by mothers in caring for children with disabilities (Leung, 2020;Harita & Chusairi, 2022). Social support is a very important element in a good communication system.…”
Section: Social Supportmentioning
confidence: 99%
“…Sehingga orang tua menganggap anak mampu melakukan sesuatu yang tidak bisa ia lakukan. Kedua, berasal dari luar (ekstern) berupa lingkungan yang tidak memadai akibat faktor ekonomi, tekanan hidup yang seolah menuntut karena terusnya mengalami peningkatan sehingga menciptakan perasaan kecewa dan marah dalam diri orang tua akan ketidakberdayaan mengatasi masalah ekonomi sehingga meluapkan emosi kepada orang-orang di sekitarnya seperti anak (Erniwati & Fitriani, 2020).…”
Section: Melakukan Tindak Kekerasan Dalam Bentuk Verbalunclassified